EXPLORING THE INFLUENCE OF ENTREPRENEURIAL EDUCATION AND ENVIRONMENT ON ENTREPRENEURIAL READINESS: THE MEDIATING EFFECTS OF ENTREPRENEURIAL MINDSET AND FINANCIAL LITERACY IN SHAPING STUDENT INTENTIONS - Koraag, Satrio Tegar Gunung; Zaki, Ahmad; Rahmawati, Syakira Alika; Oktafiani, Bintang (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study examines the influence of entrepreneurship education and the entrepreneurial environment on students' entrepreneurial mindset, financial literacy, intention, and readiness. Using a quantitative approach, data were collected from 482 university students in Indonesia through a structured questionnaire. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationship between variables. The results indicate that entrepreneurship education and a supportive entrepreneurial environment contribute to developing students' entrepreneurial mindset and financial literacy, enhancing their entrepreneurial intention and readiness. Furthermore, the study confirms that entrepreneurial intention is key in determining students' preparedness for entrepreneurial activities. These findings highlight the need for universities to strengthen entrepreneurship curricula by integrating experiential learning, financial literacy training, and mentorship programs. Enhancing the entrepreneurial ecosystem within universities can further support students transitioning to entrepreneurial careers. This research provides valuable insights for educators and policymakers to improve entrepreneurship education and foster entrepreneurial readiness among students.JEL: L26, A22.